Representing development history in software cities - Frank Steinbrückner; Claus Lewerentz (SoftVis'10: Proceedings of the Symposium on Software Visualization, 2010)
In this paper we describe a systematic approach to utilize the city metaphor for the visualization of large software systems as evolving software cities. The main contribution is a new layout approach which explicitly takes the development history of software systems into account and makes history directly visible in the layouts. These layouts incrementally evolve in a very smooth and stable way during the development of the represented software system. They are used as a visualization platform for integrating a large variety of product and process data and thus create a coherent set of specialized visualizations. To illustrate this we present some example maps capturing specific development history aspects.